Healing Trauma with metta: Nepali Texts in the Nepali Context (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
Nepali society for more than one and half decades has been under panicked condition losing many lives and property which remained irreparable for a long time. It is our memory that helps us reminisce those horrible past events from which one can hardly get rid of, thus, we are inflicted with the memories – traumatic memories that neither let us get rid of it nor let us live out of. We, as part of this painful past, have been with this reality. Many survivors have imbibed this fact in the form of printed media – writing memoirs, stories, novels, poems, etc, from which one can be aware of many such details which make us feel even more traumatic. One can’t live with this memory for a long time; thus, one needs a recovery of such painful past memory; for that a Buddhist tool can be a cure – metta.Crossing the Border: International Journal of Interdisciplinary Studies Vol.4(1) 2016: 45-52